Flowering of coffee trees under management of irrigation, side of sun exposure and positions in the plant - Custódio, Anselmo Augusto de Paiva; Lemos, Leandro Borges; Mingotte, Fábio Luiz Checchio; Barbosa, José Carlos; Pollo, Gustavo Zanetti; Santos, Henrique Menezes (Coffee Science - ISSN 1984-3909, 2014)
We investigated different irrigation managements about some reproductive characteristics of coffee plants in two sides of plant exposure to solar radiation (SPESR) and three positions in the plant. The experiment in randomized sub divided plots with four replications in a randomized block design was conducted in Matão, state of São Paulo, Brazil, in 2010/2011 harvest season. The primary treatment was six irrigation management: NI=no irrigation; CI=continuous irrigation all year round; CI 14a-19m=CI, except between april 14 to may 19; CI 20m-24jn=CI, except may 20 to june 24; CI 25jn 30jl =CI, except between june 25 to july 30 and CI 31jl-04s=CI, except between 31 july to 04 september. The secondary treatments were SPESR: southeast and northwest. The ternary treatments were the position in the plant: upper third, mid third and lower third. We evaluated the number of branches, number and percentage of flowers, number and percentage of fixation fruit and drop fruit. Irrigated plants occurs the same number and intensity of flowering plants compared to non-irrigated, but these occurs in different time and earlier. In SPESR northwest have a higher number of branches and flowers; however minor percentage of fixation fruit. The position in the plant located in the middle and upper promotes, respectively, greater fixation and drop fruit. In non-irrigated plants there is no difference in the number of flowers on the position; however occurs a lower concentration of flowering at SPESR northwest. Irrigated plants have a greater number flowers occurring in the upper third of the lower third.